A survey on the leadership among the seven urban barangay captains in the municipality of Palo, Leyte - Gabiana, Gerry G.; Tibo, Richa de los Santos (1997)
This paper is a study about the leadership patterns of the seven urban barangay captains in the locality of Palo, Leyte. These seven barangays will include Buri, Naga-Naga, Cavite East, Cavite West, Luntad, San Miguel and Sta. Cruz.
The objectives of this study are the following: (a) to identify the nature of leadership among the seven barangay captains in the municipality of Palo, Leyte, (b) to determine the relationship of the barangay captains toward their constituents and finally, (c) to find out some accomplishments of the barangay captains during their term of office.
In this study, there are three dimensional situations of a powerful and influential leader. These are the (1) Leader-Subordinate Relationship,(2) Structuring of Task, (3) Power Position.
A Leader-Subordinate Relationship focuses on the day-to-day interaction between the leader and his constituents. If the leader is desired, respected, trusted and is able to elicit loyalty and commitment from his subordinates, then he is a powerful and influential leader.
Structuring of Task on the other hand, refers to the well-structured and clearly spelled-out assignments given by the leader to his followers. This focuses on the ability of the leader to divide the task among his constituents. The leader should make sure that the work is carried out on time.
Power Position on the other hand, attributed to the output performance of the leader in the barangay. Output performance is usually associated with achievement.Achievement means the fulfillment of one's project and programs. Development, on the other hand, is something that surpasses progress and raises the standard of living of the people.
This study conducted through the use of questionnaire. It is a combination of both open-ended and close-ended questions. The data that are gathered by the researchers are information ranging from Leader-Subordinate Relationship, the Assessment of Colleagues about the barangay captains, and Output Performance of the local chief executives.
On the demographic profile of respondents, the data shows that their age ranges from 18 to 79 years old. Majority (25) of the respondents fall under the age bracket ranging from 41 up to 50 years old. In terms of Sex and Civil Status, majority are women which comprise 55.8 percent while the remaining 44.2 percent are males. On the other hand, 51.2 percent of the respondents are married while 36.4 percent are still single and 7.8 percent are widow/er while the remaining 4.6 percent of respondents abstain from stating their civil status.
Based on the result of the survey, by and large, the responses are in favor to the seven barangay captains, hence they are quite effective to their jobs.
Undergraduate thesis (B.A.S.S. Political Science)-- University of the Philippines, Tacloban.
Keywords: Leadership patterns -- Barangay captains -- Philippines -- Palo, Leyte